2017
DOI: 10.1016/j.mseb.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A study of long-term static load on degradation and mechanical integrity of Mg alloys-based biodegradable metals

Abstract: Predicting degradation behavior of biodegradable metals in vivo is crucial for the clinical success of medical devices. This paper reports on the effect of long-term static stress on degradation of magnesium alloys and further changes in mechanical integrity. AZ31B (H24) and ZE41A (T5) alloys were tested to evaluate stress corrosion cracking (SCC) in a physiological solution for 30 days and 90 days (ASTM G39 testing standard). Scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, there are no systematic studies on the mechanical properties of the degradation layer. It appears very fluffy and brittle, 60,63 and it has been reported several times that part of the very thin degradation layer can exfoliate. 64 However, some of the cracks visible in microscopic images may only be drying artefacts.…”
Section: Degradation In Presence Of Cellsmentioning
confidence: 99%
“…However, there are no systematic studies on the mechanical properties of the degradation layer. It appears very fluffy and brittle, 60,63 and it has been reported several times that part of the very thin degradation layer can exfoliate. 64 However, some of the cracks visible in microscopic images may only be drying artefacts.…”
Section: Degradation In Presence Of Cellsmentioning
confidence: 99%
“…For orthopedic and cardiovascular implants, materials are often also subjected to complex stress environments in vivo, including tension, compression, bending, and cyclic mechanical loadings [ 18 , 19 , 20 ]. For example, a bone plate needs to bear certain tensile stress for connecting the fractured bones together [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, SCC is related to anodic dissolution and hydrogen embrittlement [ 105 , 106 , 107 , 108 , 109 ]. It is suggested that the anodic dissolution with intergranular stress corrosion feature can be attributed to the micro-galvanic activity between grain boundary second phases and the adjacent matrix [ 105 , 108 , 110 , 111 , 112 ]. The corresponding corrosion susceptibility can be increased by the electrochemical thermodynamic activity, rupture of the surface layer, and dislocations piling up in grain boundaries or internals [ 113 ], accompanied by localized corrosion/pits [ 108 ].…”
Section: Corrosion Behaviormentioning
confidence: 99%